Histopathological changes in turbot Scophthalmus maximus due to a histophagous ciliate - Dyková, Iva; Figueras Huerta, Antonio (Inter Research, 1994)
5 pages, 13 figures. Histological examination of moribund specimens of turbot grow-out facilities in northwest Galicia (Spain) revealed lesions severe enough to be responsible for the diseased condition and death of many fish. The lesions were caused by 2 agents, the microsporidian Tetrarnicra brevifjlum, already described from the same host farmed in the same region and a histophagous ciliate. Both agents were found In mlxed infections; the dominant role in pathogenesls was played by the histophagous ciliate which was tentatively assigned to the subclass Hymenostomata, order Scuticociliatida Small, 1967. Peer reviewed